The Effect of Ceramic Thickness and Number of Firings on the Color of Two All-Ceramic Systems Measured by Spectrophotometer - Zaid A Al Marah; Haitham J Al-Azzawi (College of Dentistry/ University of Baghdad, 2016)
Background: This in vitro study was carried out to evaluate the effects of various veneering dentin ceramic thicknesses and repeated firings on the color of lithium disilicate glass-ceramic (IPS e.max Press) and zirconium-oxide (IPS ZirCAD) all-ceramic systems, measured by clinical spectrophotometers (Easyshade Advance 4.0) . Materials and methods: The 72specimens cube-shaped have the dimension of about 11 mm in width, 14 mm in length, 1mm in thickness, these cores divided into 3 groups according to the type of material each group have (24)core specimens. Each group had been divided into three sub-groups (each having 8 specimens) according to veneering with dentin ceramic thicknesses: as 0.5, 1, or 2 mm (n=8). IPS e.max press and ZirCAD cores group had been veneered with IPS e.max Ceram dentin ceramic shade A2 according to manufacturer's instructions and the metal group had been veneered with IPS classic dentine ceramic with shade A2 according to manufacturer's instructions. Repeat firings (3, 5 and 7 times) had been applied on all the specimens. Color differences among ceramic specimens had been measured using a clinical spectrophotometer (VITA Easyshade); the color data had been expressed according the Vita Classic shade guide. Results: The shade of all specimens had been compared inside the subgroups and with the main groups. The percentage of color agreement among the subgroups showed the color of all ceramic systems had been affecting by firing interval, the ceramic thickness and brand of ceramic. The number firings intervals applied on the all ceramic system has a significant effect on the final color, the increase of firing number change the color to a darker and reddish color. The 5th firing interval is the point at which the major color changes happened (darker shade), and in next interval (7th firing) less color changes happened. The thickness of veneering ceramic affected the color significantly. The 0.5 mm specimens in all groups showed the highest percentage of agreement (less color changes) after firing intervals, then the 1mm came and the least percentage of agreement ( highest color changes ) was the 2 mm specimens. The Brand of veneering ceramic and the type of core record a significance difference in color changes when exposed to firing heat. Conclusion: With limit of this study, the final color of the all ceramic system definitely affected by the number of firing cycle exposed to, and the veneering ceramic thickness have a clear effect on the final shade of the all ceramic tested.